Community based seed production through IRRI /IAAS projects in western mid hills of Nepal: A review - Adhikari, Bishnu Bilas (Journal of Agriculture and Natural Resources, 2020)
A review on the community based seed production through IRRI/IAAS projects was made to know the seed production situation in western mid hills of Nepal. In Nepal, around 90% of seeds are supplied through informal sector where seed replacement rate (SRR) of major staple food crops is around 10%. The formal seed supply systems are characterized by a vertically organized production and distribution of released or registered varieties by public and private organizations using agreed quality control mechanism. Community Based Seed Production (CBSP) is one of the most important community resources from which, small holder farmers can improve their livelihoods which serves as a means to attain food and nutrition security and income generation to the farmers. IRRI/IAAS collaborative projects (IFAD TAG 706, STRASA and CURE) have establish 15 CBSP organizations in Lamjung, Tanahun, Gorkha and Bajhang district since 2006 to 2014 and producing quality seed annually. Project team has developed a unique type of working modality to get success in research, development and technology dissemination. Conduction of PVS trial annually in key sites, regular training to farmers, exposure visit of farmers, monthly meeting with farmers, regular minikit distribution in new sites, award to best seed producers, collaborative work with respective DADOs are some examples. Though CBSPs have faced major challenges like limitation of fund for seed buying, availability of quality source seed in time and place, availability of machines like moisture meter, grading machines, weighing machines, seed storage problems, marketing problems, natural disasters etc. the projects have contributed in release of rice varieties like Ghaiya-2, Sukhadhan series from 1 to 6, Bahuguni, Hardinath-2 and Chiyarang sub-1 as drought tolerant, and Ramdhan, Sunaulo sugandha, Mithila, Swarna sub 1 and Barkhe 1022 as irrigated varieties during project period.